Variability of blood eosinophil count and prognosis of COPD exacerbations - Sandra Martínez-Gestoso; María-Teresa García-Sanz; Uxío Calvo-Álvarez; Liliana Doval-Oubiña; Sandra Camba-Matos; Francisco-Javier Salgado; Xavier Muñoz; Purificación Perez-Lopez-Corona; Francisco-Javier González-Barcala (Annals of Medicine)
Background Eosinophils in peripheral blood are one of the emerging biomarkers in chronic obstructive pulmonary disease (COPD) patients. However, when analysing the relationship between peripheral eosinophilia and COPD prognosis, highly variable results are obtained. The aim of our study is to describe the serum eosinophilia levels in COPD patients and to analyse their relationship to prognosis following hospital admission.Methods A prospective observational study was conducted from 1 October 2016 to 1 October 2018 in the following Spanish centres: Salnés County Hospital in Vilagarcía de Arousa, Arquitecto Marcide Hospital in Ferrol and the University Hospital Complex in Santiago de Compostela. The patients were classified using three cut-off points of blood eosinophil count (BEC): 150 cells/µL, 300 cells/µL, and 400 cells/µL; in addition, the peripheral BEC was analysed on admission.Results 615 patients were included in the study, 86.2% male, mean age 73.9 years, and mean FEV1 52.7%. The mean stay was 8.4 days, and 6% of all patients were readmitted early. No significant relationship was observed between the BEC, neither in the stable phase nor in the acute phase, and hospital stay, readmissions, deaths during admission, the need for intensive care, or the condition of frequent exacerbator.Conclusion The results of our study do not seem to support the usefulness of BEC as a COPD biomarker.KEY MESSAGESThere is evidence that BEC participates in pathophysiological mechanisms of the COPD.BEC may be useful as a biomarker in COPD for aspects such as the optimization of treatments.We did not find any relationship between BEC levels and prognosis following hospital admission for AECOPD.